INCORPORATING CRITICAL THINKING SKILLS INTO AN ENGLISH TEXTBOOK FOR JUNIOR HIGH SCHOOL STUDENTS OF SEMARANG CITY (Universitas Negeri Semarang, 2015)
The objective of this study is to find out whether the use of English textbook which deliberately incorporatescritical thinking skills into its tasks is effective to promote critical thinking skills to the students of Semarang City. This study is based on the theory that critical thinking skills can be nurtured and the process of nurturing should be done directly and explicitly. A research and development (R and D) approach was utilized as the design of this study and the development of the textbook model was based on the results of the analysis of the existing English textbooks for junior high school students and the needs analysis. The prototype was validated by experts and practitioners before it was tried-out in a state school in Semarang. In the examination phase, an experimental research was conducted to the students and the teachers of three different schools in Semarang in the odd semester of the academic year of 2013/2014.The results showed that the students taught using the model had better results of critical thinking skills assessment than those who were not. With sensitive feedbacks and aids given by teachers, the students also showed a more active involvement in the learning process.